Zmiany na rynku jaj i perspektywy jego rozwoju - Urban, Stanisław (Changes on the Egg Market and Perspectives of Its Development, 2005)
In Poland egg production concerns mainly hen eggs. Most eggs come from big farms and their share in the total production is still on the increase. Even though the numer of eggs obtained from one hen is low it is steadily increasing. Eggs are mainly used for consumption and food processing. As far as the import is concerned, it is low whereas low so far export has distinctly grown after the EU accession. Furthermore egg processing i salso increasing and processed eggs are one of the subjects of Polish export. On the other hand the eggs consumption in Poland is lower than in the other 15 EU countries. However, in the last few years it has been rapidly increasing. Prospects for the development of this branch of economy are: the production of ecological eggs, egg processing and keeping other species then hens for obtaining eggs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 375-381